Tutorials for the general practice registrar - Warren, Edward (Butterworth-Heinemann, 2002)
The book is prepared specifically to help the busy GP trainer ensure trainees get the most out of their tutorial time. Learning objectives are given for each tutorial, ensuring the knowledge, skills and attitudes of the trainee are tested. The topics covered include the common areas of practice and those areas that trainees traditionally struggle with. Those intending to take the MRCGP examinations will find these tutorials to be a useful review aid